2014
DOI: 10.1371/journal.pone.0104025
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Attentional Bias to Threat in Anxious Adults: Bias towards and/or Away?

Abstract: The aim of the present study was to question untested assumptions about the nature of the expression of Attentional Bias (AB) towards and away from threat stimuli. We tested the idea that high trait anxious individuals (N = 106; M(SD)age = 23.9(3.2) years; 68% women) show a stable AB towards multiple categories of threatening information using the emotional visual dot probe task. AB with respect to five categories of threat stimuli (i.e., angry faces, attacking dogs, attacking snakes, pointed weapons, violent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 58 publications
3
84
0
Order By: Relevance
“…A dot-probe study with a stimulus set of pictures of angry faces, attacking dogs, attacking snakes, pointed weapons and violent scenes showed that 34% of the participants showed a general bias toward threat and 20.8% showed a general bias away from threat. However, 34% of the participants showed a bias toward some categories and away from other categories (Zvielli, Bernstein, & Koster, 2014). Whether the same pattern in individual differences can be found for biases for different negative faces needs to be investigated.…”
Section: Types Of Stimulimentioning
confidence: 98%
“…A dot-probe study with a stimulus set of pictures of angry faces, attacking dogs, attacking snakes, pointed weapons and violent scenes showed that 34% of the participants showed a general bias toward threat and 20.8% showed a general bias away from threat. However, 34% of the participants showed a bias toward some categories and away from other categories (Zvielli, Bernstein, & Koster, 2014). Whether the same pattern in individual differences can be found for biases for different negative faces needs to be investigated.…”
Section: Types Of Stimulimentioning
confidence: 98%
“…It is well known that anxiety disorders are associated with maladaptive changes in information processing due to an attentional bias (Bar-Haim et al, 2007;Mogg & Bradley, 1998)characterized by pre-attentive shifts in attention and enhanced processing of threat-related cues (Koster, Crombez, Verschuere, Van Damme, & Wiersema, 2006;Zvielli, Bernstein, & Koster, 2014). Here, it seemed that high trait anxiety was linked to deeper/more effortful acoustic processing of non-linguistic vocalizations (promoting stronger N1 amplitudes for vocalizations), followed by a broadbased increase in the deployment of attention to all vocal emotion expressions to determine their motivational relevance (i.e., increased P2 amplitudes to both vocalizations and speech in individuals with high versus low trait anxiety).…”
Section: Effects Of Anxiety On Vocal Emotion Processingmentioning
confidence: 99%
“…As a first step in the dot probe data preparation, in line with previous research (e.g., Zvielli, Bernstein, & Koster, 2014), all trials with errors and reaction times (RT) faster than 200 and slower than 1500ms were removed (2.16%). Generally accuracy was high (M = 97.98%, SD = 1.70%, range = 92% -100%).…”
Section: Resultsmentioning
confidence: 99%
“…Attentional bias variability is one of the TL-BS measures 1 . Attentional bias variability for threat and safety was calculated using the computation code as used in Zvielli et al (2014). This code subtracts RTs between temporally contiguous matched trials (incongruent vs. congruent) so that attentional bias can be estimated at trial-level.…”
Section: Resultsmentioning
confidence: 99%